An FPT.AI-Based Text-to-Speech Application's End-to-End Conversion Speed Analysis (International Journal of Innovative Research in Engineering & Management, 2022)
In this paper, an FPT.AI-based text-to speech (TTS) application is developed that converts  Vietnamese text into spoken words. the applying is  developed supported Django for Python ANd within the  style of AN interactive website that is connected to an  FPT.AI server through its application programming  interface (API). the applying supports conversion of text  to seven totally different Vietnamese speeches. Four out  of seven voices are often wont to convert up to five  hundred characters in an exceedingly single group action  whereas the others support that of four hundred  characters. supported the results obtained, the primary  conversion time takes up to ten s to convert 400- character text into speech whereas the following times,  given same text, it takes beneath one.8 s for the  conversion. this is often applicable to any or all voices.
Keywords: FPT.AI; TTS; performance; analysis; Vietnamese; voice